PELESTARIAN ARSITEKTUR MASJID AGUNG LAMONGAN SEBAGAI UPAYA PEMELIHARAAN IDENTITAS DAERAH - Agustapraja, Hammam Rofiqi (Universitas Aisyiyah Yogyakarta, 2019)
The Lamongan Great Mosque is a witness to the development of the Islamic symbol in Lamongan City, located west of the Lamongan City Square. This mosque gives a religious visual character to the area. This mosque was built in 1908 and experiences developments and changes along with the needs of the function, so it needs there is an effort to preserve architecture so that its historical value is maintained and becomes the regional identity. The purpose of this study is to identify and analyze building characteristics and to identify and analyze the direction of the preservation of the Great Mosque of Lamongan. This study uses three kinds of descriptive methods, including descriptive analysis methods, evaluative methods, and development methods. Analysis of building characters in this study include spatial characters, visual characters, and structural characters. The three-character analyzes are used as sources for analyzing the preservation direction of the mosque. Potential directives for preservation can be divided into three, namely high potential with preservation and conservation preservation directives, moderate potential with conservation and rehabilitation preservation directives, and low potential with rehabilitation preservation directives.